(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
This study is devoted to the linguistic analysis of reactive utterances and their semantic groups in dramatic text. In the paper, a reactive utterance is interpreted as a speech unit that is formed in semantic relation to a preceding stimulus utterance during dialogue, ensures the semantic coherence of communication, and determines the further development of conversation. The research distinguishes declarative, interrogative, and imperative types of reactive utterances, and each of them is consistently analyzed from structural-semantic, communicative, and pragmatic perspectives. In particular, interrogative reactive utterances are examined through their clarifying, confirmatory, counter-question, and doubt-assumption forms, while imperative reactive utterances are illustrated with examples of dispute-closing, soft prohibition, and emotive types. As a result, the reactive utterance in dramatic text is scientifically substantiated as an important linguistic unit constituting dialogue, while its semantic groups are identified as the main mechanisms ensuring the semantic and pragmatic development of communication.